Persistence of hepatic hepatitis B virus after serological clearance of HBsAg with autologous peripheral stem cell transplantation. Issue 8 (August 1997) - Lau, G K; Wu, P C; Liang, R; Yuen, S T; Lim, W L
Abstract : Delayed clearance of hepatitis B surface antigen was previously reported in a 38 year old woman after high dose chemotherapy with autologous peripheral blood stem cell rescue. Sixteen months later, this patient remained hepatitis B surface antigen negative, hepatitis B surface antibody positive, and serum hepatitis B DNA negative by polymerase chain reaction. Serial liver biopsies (one at hepatitis B e antigen positive stage, one at hepatitis B e antibody positive stage, and one at hepatitis B surface antigen negative and hepatitis B surface antibody positive stage) showed a gradual resolution of the inflammatory activity with loss of hepatitis B e antigen and then hepatitis B surface antigen in the serum. However, the degree of fibrosis, though mild, remained the same. With the serological clearance of hepatitis B surface antigen, a small amount of hepatitis B virus DNA was still detectable in the nuclei of liver cells.